Hydrothermal carbonization and Liquefaction: differences, progress, challenges, and opportunities - Lachos-Perez, Daniel; César Torres-Mayanga, Paulo; Abaide, Ederson R.; Zabot, Giovani L.; De Castilhos, Fernanda (Bioresource technology, 2022)
[Display omitted] •The feasibility of handling lignocellulosic biomass via HTC/HTL were reviewed.•The yield of hydrochar/ bio-crude can be improved by altering HTL/HTC conditions.•Reaction mechanism of HTL/HTC is explained.•HTC and HTL suffer from immature technology, demanding innovations. Thermochemical processes including hydrothermal technology are gaining research interest as a potentially green method for deconstructing biomass into platform chemicals or energy carriers. Hydrothermal liquefaction (HTL) and Hydrothermal Carbonization (HTC) are advantageous because of their enhanced process performance while being environmentally friendly and technologically innovative. However, after a deep review, several works have shown a misunderstanding between HTL and HTC concepts. Therefore, this review advances understanding on the main differences and gaps found between HTL and HTC in terms of operation parameters, technical issues, and main products. Furthermore, environmental and techno-economic assessments (TEA) were presented to appraise the environmental sustainability and economic implications of these techniques. Perspectives and challenges are presented and the integration approaches of hydrothermal valorization pathways and biorefining are explored.